Experimental and numerical investigations of the bubble collapse at the center between rigid walls. (November 2015) - Ogasawara, T; Tsubota, N; Seki, H; Shigaki, Y; Takahira, H
Abstract: The collapsing behavior of a bubble generated at the center of the rigid walls and its effect on the wall are investigated experimentally and numerically. The bubble collapse drastically depends on the ratio of the gap width to the maximum bubble radius w *. In case of 2.66 < w * < 1.17, by the decrease in w * to 2.5, the splitting collapse occurs; the bubble splits into two at the center of the gap during collapse and each bubble collapses near the wall with the translation toward nearer wall. Further decrease in w * to 1.4 causes neutral collapse where the bubble collapses at the center of the gap without splitting and translation. These collapsing behaviors are successfully simulated by considering the bubble shape at the maximum bubble volume. The peak pressure on the wall decreases by the transition of the collapsing behavior from the splitting collapse to the neutral collapse due to the decrease in w *, which indicates the wall damage reduction due to the neutral bubble collapse in thinner gap.